FUZZY GAIN SCHEDULING: COMPARISON OF THE CONTROL STRATEGY (2022)
The use of better control strategies has a great interest in all kinds of industries in recent years since it allows better use of resources and therefore becomes an important factor in reducing costs associated with reprocessing and unnecessary spending of raw materials. This research evaluates the performance of a control strategy, in which the tuning parameters of a classic controller are supplied by a fuzzy logic algorithm (Fuzzy Gain Scheduling). the behaviour of the strategy is tested in a mixer-reactor system and is compared with that achieved through the implementation of a classic controller, a dynamic matrix system, and fuzzy logic control. In the results, it can be seen that the Fuzzy Gain Scheduling strategy presents a good behaviour, improving around 25% compared with the other alternatives, this added to the advantage of being able to include previous experience on the process, in the actions that are taken by the strategy to keep desired operating ranges. © 2022 School of Engineering, Taylor's University.